Soft Power Diplomacy Through Halal Certification in Enhancing the Competitiveness of Riau’s Food Products in the International Market - Roza Andriani; Amri Hakim; Hariy Laksamana (Jurnal Hubungan Internasional, 2025)
Halal certification has evolved from a mere administrative requirement into a strategic instrument of public diplomacy and soft power. As the world’s largest Muslim-majority country, Indonesia has the potential to leverage halal certification to enhance the competitiveness of its food products in international markets. However, at the subnational level, particularly in Riau Province, which shares direct borders with Malaysia and Singapore, its implementation faces significant challenges. This research examined the role of halal certification as a tool of soft power diplomacy in enhancing the competitiveness of Riau’s food products. Current discourse on halal diplomacy tends to concentrate on the national level, leaving the role of subnational actors such as local governments and MSMEs underexplored. To address this gap, the research employed a qualitative descriptive-analytical approach. Data were collected through document analysis and in-depth interviews with the Halal Product Assurance Organizing Body (BPJPH), the Assessment Institute for Foods, Drugs, and Cosmetics of the Indonesian Ulema Council (LPPOM MUI), local government agencies, and MSME food producers. The analysis revealed that halal certification has served a dual role, acting as both affective soft power through Islamic values and cultural appeal, and as normative soft power, providing global legitimacy and consumer trust. Accordingly, halal certification serves as a medium of public diplomacy, strengthening Indonesia’s position within the global halal economy. Theoretically, the research extends the application of soft power to subnational contexts. Practically, it recommends policies for facilitating certification, harmonizing standards, and building MSME capacity.